2015
DOI: 10.1177/2053168015612247
|View full text |Cite
|
Sign up to set email alerts
|

Desirable pork: do voters reward for earmark acquisition?

Abstract: The overwhelming majority of Congresspersons engage in the acquisition of pork projects, also known as earmarks. In the aggregate, the general public overwhelming opposes pork-barrel spending, yet scholars and Members of Congress both contend that earmarked projects make for grateful constituents. This work attempts to explain this discrepancy. Using experimental data, I show that general discussions of earmarks are not universally beneficial. Recipients are only moved when they are made aware of projects in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In his experiments conducted in Denmark, Bøggild (2016) observed that subjects respond to the reelection efforts of politicians who use the impartial distribution of public finances with a lower level of trust and reduced willingness to vote for these politicians even when they can benefit from distribution. However, this conclusion is not fully in line with the outcomes of experiments organized in the United States by Travis Braidwood (2015). In these experiments, "[r]ecipients are only moved when they are made aware of projects in policy arenas of individual importance.…”
Section: Voters' Perceptions Of Pork-barrel Politicsmentioning
confidence: 94%
See 3 more Smart Citations
“…In his experiments conducted in Denmark, Bøggild (2016) observed that subjects respond to the reelection efforts of politicians who use the impartial distribution of public finances with a lower level of trust and reduced willingness to vote for these politicians even when they can benefit from distribution. However, this conclusion is not fully in line with the outcomes of experiments organized in the United States by Travis Braidwood (2015). In these experiments, "[r]ecipients are only moved when they are made aware of projects in policy arenas of individual importance.…”
Section: Voters' Perceptions Of Pork-barrel Politicsmentioning
confidence: 94%
“…However, as some other studies show, this mechanism may not apply under all circumstances; sometimes voters can tolerate or overlook unfair decision-making, especially in situations in which they themselves are benefiting from the outcomes of these policies (Braidwood 2015;Tyler 1990). As Brockner and Wiesenfeld (1996, 191) noted, "when procedural justice is relatively low, outcome favorability is more apt to be positively correlated with individuals' reactions."…”
Section: Policy Support Hypothesis (3)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, perception of pork barrel may be positively biased if individuals benefit from such practices. The literature supports (Braidwood, 2015; Brockner and Wiesenfeld, 1996; Tyler, 1990: 98–102), but also rejects such a reasoning (Bøggild, 2016; Lind, 2001: 59–60). Nevertheless, the conditions of our experiment require us to consider this factor.…”
Section: Theoretical Frameworkmentioning
confidence: 99%